Modelo de Gestão da Sustentabilidade para um Laboratório de Análises Clínicas - Bordignon, Cristina Aparecida Nunes (2023)
This study presents the application of a Sustainability Management Model for a clinical analysis laboratory. The organization in this study has been given the fictitious name of Delta Laboratory to preserve its anonymity. The aim is to propose a Sustainability Management Model aimed at defining environmental policy and sustainable actions applied to a clinical analysis laboratory in a municipality in the western region of Paraná. In order to answer the research problem and meet the related objectives, the methodology was configured in a qualitative way, being descriptive research that adopts the case study as a method of procedure, interview, systematic observation and documentary research as a data collection technique. To apply the Sustainability Management Model, we used Backer's (2002) ecological strategy diagnosis, the Corporate Environmental Policy (PAE) tool by Andrade, Silveira, Santos and Meneghatti, (2021), to draw up an environmental policy appropriate to the organizational objectives and strategy, and Anvisa's RDC 222/2018 checklist to verify the health service waste management practices developed by the author. The method used made it possible to diagnose the weaknesses and strengths of sustainability management and to plan improvement actions related to integrating environmental policy through sustainable practices. Eighteen sustainable action plans were drawn up for the organization in the sectors of corporate ecological strategy, communication and marketing, production, human resources, legal, finance, research and development, waste management, among others. This research contributes to raising awareness and applying sustainable practices at Delta Laboratory. The proposed model proved to be suitable for the organization and can be applied to organizations in the same sector of activity